CENTRAL ELLIPSOID LOSS ASSOCIATED WITH CONE DYSTROPHY AND KCNV2 MUTATION. (2018) - Xu, David; Su, Daniel; Nusinowitz, Steven; Sarraf, David
Abstract : Purpose: To report a case of central ellipsoid loss with supernormal rod electroretinogram and KCNV2 gene mutation. Methods: Retrospective case report. Patient: Thirty-eight-year-old man. Results: We report a patient with longstanding vision loss and photophobia who illustrated central atrophy of the inner segment ellipsoid zone band on spectral domain optical coherence tomography. Fundus autofluorescence displayed mild perifoveal mottled autofluorescence. Electroretinography demonstrated a diminished rod-isolated response with delayed timing but a normal dark-adapted maximal response to bright flashes. Cone-mediated responses under light-adapted conditions were abnormal with evidence of selective loss of the b wave and a normal a wave consistent with cone dystrophy with supernormal rod electroretinogram. Genetic testing demonstrated a frameshift mutation in the KCNV2 gene. Conclusion: Cone dystrophy with supernormal rod electroretinogram is believed to be a monogenic disease due to KCNV2 gene mutations that affect a transmembrane potassium channel found in rod and cone photoreceptors. We report the multimodal retinal findings associated with a signature electroretinogram in this disorder. Clinicians should consider this rare condition when evaluating patients with central ellipsoid loss and associated cone dystrophy. Abstract : A patient presented with longstanding vision loss. Optical coherence tomography analysis was remarkable for central ellipsoid loss. Electroretinography was notable for cone dystrophy with supernormal rod electroretinogram, and genetic testing was positive for a KCNV2 gene mutation. Cone dystrophy with supernormal rod electroretinogram is associated with a signature electroretinogram illustrating a severely depressed rod response to dim light that normalizes with a bright flash exposure.